Catalogue of marine mammals of the Mammalogical collection of the Museo de La Plata, Argentina - Olivares, Adriana Itatí (2016)
This catalogue lists the materials of marine mammals housed in the Mammalogical collection of Museo de La Plata. This contribution is an update of the unpublished catalogue made by R. Bastida, J.B. Desojo, and L.H. Soibelzon in 1997. It includes all the specimens deposited in this collection, belonging to the superorder Cetartilodactyla, order Cetacea, suborders Mysticeti and Odontoceti, the order Carnivora, suborder Caniformia, and the order Sirenia. The Mammalogical collection of the División Zoología Vertebrados of Museo de la Plata holds 185 specimens of 37 species of marine mammals.